POCIĄGI ŚMIERCI – kilka uwag o konstrukcji hasła słownikowego - Buryła, Sławomir (Narracje o Zagładzie [czasopismo zamknięte], 2016)
DEATH TRAINS – Some Notes on the Construction of the Dictionary Entry The article discusses the topos of the death train in Polish literature and collective imagination. In the first part, the author presents the genesis of the topos and reconstructs its meanings. In the second part, he focuses on the specific problems related to including the entry in the future dictionary of the topoi of the Holocaust. The topos of the death train is one of the oldest ones in the collection of the Holocaust‑related themes. It is often perceived as a synonym to the Shoah. The author of the article enumerates and briefly interprets the most significant literary and cultural examples of the death trains. Key words: Literary topos, Holocaust, Holocaust literature